The Political Party Phenomenon as the Major Underpinning and at Times a Conduit for the Demise of Democracy&Rechtstaat - Mik STRMECKI (Transylvanian Review of Administrative Sciences, 2007)
Political parties are torn between the Scylla of their over-incorporation into the State mechanism with the ensuing possible impairment of their independence from the State and the Charybdis of their under-regulation, resulting in legal and/or constitutional lacunae iuris leading to anomalies detrimental to the public interest in maintaining the survival of a viable parliamentarian democracy imbued with the principles of freedom, fairness, equality and the Rule of Law. In my article I presented a historical and comparative insight into the so-called Four-phase theory, spearheaded by Heinrich Triepel on the treatment of the political party phenomenon by the State, namely: oppression, ignorement, legalization and constitutionalisation. I also presented a survey of individual countries constitutional and legal approaches in regulating the political party phenomenon by citing definitions along with typical functions, which I then analyzed by discerning private ones from public ones. I then went on and gave an insight and description of the so-called syndrome of the political market quagmire and concluded my article by illuminating the problem of surveying legitimate legal grounds for banishment of political parties under German and Slovenian law.